ORGANOGENESIS TANAMAN JABON MERAH (Anthocephalus macrophyllus (Roxb) Havil) PADA BERBAGAI KONSENTRASI KOMBINASI IAA (Indole Acetid Acid) DAN BAP (Benzyl Amino Purin) SECARA IN VITRO - Marzuki, Sahriana; Muslimin, Muslimin; Irmasari, Irmasari (Jurnal Warta Rimba, 2016)
This research was conducted by applying Complete Random Design (Rancangan Acak Lengkap /RAL) that consisted of 4 treatments: JM1= 2  mg/l BAP +  0,1 mg/l IAA, JM2= 4  mg/l BAP + 0,3 mg/l IAA, JM3= 2  mg/l BAP + 0,3 mg/l IAA, JM4= 4  mg/l BAP + 0,1 mg/l IAA. Each experiment repeated 5 times, so there were 20 units experiment done. The parameter observed was when the sprout grew, the number of sprout, the leaf revealed and the number of root that was observed at the end of the research. Qualitative data analyzed by using test variant analysis F 5% to find out whether the effect of treatment was real or not,  if it was real, multiple comparison test was done by using BNJ test in 5 % level in order  to  decide real different treatment. The organogenesis of Red Jabon (Anthocephalus macrophyllus (Roxb) Havil) in the research was occurred directly. The result of the research showed that the treatment with combination concentration of 4 mg/l BAP + 0,3 mg/l IAA (JM2) was the best one of observed parameter except the number of root. The fastest emerging buds responds and the highest buds number was 5.6 day After Planting (Hari Setelah Tanam (HST) and average of formed buds was 2.4, and the average time that  needed  to formed the leaf was 19 Days After Planting ( Hari Setelah Tanam (HST) and the number of  forming leaves were 2.8  sheets.  There was not root formed in whole conducted treatments.Key words: Red Jabon, Plant tissue culture, Organogenesis, Growth Regulator Substance, BAP dan IAA.